PSYCHOLOGY OF SPORTS: HISTORY, TYPES OF PROFESSIONALS AND AREA OF ACTIVITY (Fiep Bulletin - online, 2019)
The Psychology of Sport is a science that has great value in the contribution of the Human being in the sportive,recreational, leisure and rehabilitation. Thus, it comes in contact with the general development of the sports sciences andintervene with the human movement, consequently promoting greater and better quality of life and health to the adepts of anysport. The school environment had great gains through the Law of Guidelines and Bases of Brazilian Education (Law No.9394/96) where the commitment to the school sport was to advance in the relations and obtain great advance in the socialaspects. We also have other fields of activity such as recreational sports that prioritize well-being for all people, rehabilitationsports totally focused on prevention and intervention in people involved in sports that present some type of injury resulting fromthis sports practice, or people with physical and mental disabilities and finally we have the sport of income seeking to improve andoptimize the performance of the individual athlete in a formal and institutionalized approach. Thus it is ample and necessary theperformance of this professional that can be Psychologist or Professional of Physical Education. In this structure of highperformance sport, the sports psychologist works by analyzing and transforming the psychic determinants that interfere with theperformance of the athlete and / or sports group. This bibliographical article aims to analyze the Psychology of Sport from itsbeginning and to understand the importance of this professional in the fields of activities, demonstrate how can be a professionalwith the ability to contribute to the competent bodies and act in the multidisciplinary work with the teams